ChemInform Abstract: Defined Palladium—Phthalimidato Catalysts for Improved Oxidative Amination. Issue 41 (September 2016) - Martinez, Claudio; Muniz, Kilian
Abstract: New palladium(II)—phthalimidato complexes are synthesized, isolated, and structurally characterized.